THE RELATIONSHIP BETWEEN COMPLIANCE WITH THE USE OF APD AND NOISE INTENSITY WITH HEARING COMPLAINTS IN PRODUCTION WORKERS AT PT. BEURATA SUBUR PERSADA - Laura Amelia; Susy Sriwahyuni; Kiswanto (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2024)
Hearing loss is one of the health problems that risks reducing worker productivity. Someone who suffers from hearing loss, not only can be seen from several things such as difficulty speaking, but also can be seen from the physiological condition of the worker himself. Hearing loss can be caused by several factors including noise intensity, compliance with the use of personal protective equipment. The purpose of this study was to determine the effect of SOP compliance in the use of PPE and noise intensity on hearing complaints in production workers at PT Beurata Subur Persada. This type of research is quantitative with a cross sectional design. The research location was at PT Beurata Subur Persada. The population in the study were all workers in the production department as many as 96 workers and a sample of 49 workers. Data were analyzed with the chi square statistical test. Results: based on the results of the analysis that has been done, there is a relationship between noise intensity with subjective hearing complaints (pvalue = 0.027) and there is a relationship between SOP compliance with subjective hearing complaints (pvalue = 0.000). It is recommended that companies establish hearing conservation programs and audiometric tests for workers to prevent deafness and complaints of hearing loss due to noise exposure.